CLPTM1L DNA DNA Typing Kits and Diagnostic Kits for Detecting Cancer using Minisatellites of CLPTM1L Gene - MUN, MI HYE; LEEM, SUN HEE; JEONG, MI SO; LEE, SE RA (2018)
The present invention relates to polymorphic minisatellites of a CLPTM1L gene; and a cancer diagnostic kit and a DNA typing kit using the same. More specifically, the present invention relates to a primer set for detecting polymorphic minisatellites such as CLPTM1L-MS1, CLPTM1L-MS2, CLPTM1L-MS3, or CLPTM1L-MS4 present in the promoter region regulating the expression of CLPTM1L gene; and a cancer diagnostic kit and a DNA typing kit using the primer set. Since the polymorphic minisatellite CLPTM1L of the present invention is transferred through meiosis according to Mendel′s laws, the polymorphic minisatellites can be DNA-typed to be used for paternity test and blood relation test of a subject, or forensic evaluation; and a CLPTM1L-MS2 region is amplified to detect sensitivity to cancer by lengths of allelomorphs. 본 발명은유전자의 다형성 소위성과 이를 이용한 DNA 타이핑 키트 및 암의 진단 키트에 관한 것으로, 보다 자세하게는,유전자의 발현을 조절하는 프로모터 영역에 존재하는 다형성 소위성 소위성-MS1,-MS2,-MS3 또는-MS4를 검출하기 위한 프라이머 세트, 상기 프라이머 세트를 이용한 DNA 타이핑 키트 및 암 진단용 키트에 관한 것이다. 본 발명의다형성 소위성은 멘델리안 유전에 따라 감수분열을 통해 전달되므로 이를 DNA 타이핑함으로써 개체의 친자 확인, 혈연 확인 또는 법의학적 감정에 사용할 수 있으며,-MS2 영역을 증폭하여 대립형질의 길이에 따라 암에 대한 감수성을 진단할 수 있어 유용하다.